MCR 2009 proceedings of the 4th International Conference on Multi-Component Reactions and Related Chemistry, Ekaterinburg, Russia - Mironov, Maxim A. (Advances in Experimental Medicine and Biology, 2011)
This proceedings volume contains abstracts from MCR 2009, the Fourth International Conference on Multi-Component Reactions and Related Chemistry (Ekaterinburg, Russia). The main focus of this conference was on multi-component reactions, though its scope also embraced organic synthesis via tandem or cascade reactions, combinatorial approaches to new materials, catalysts and supramolecular structures. Multi-component reactions warrant ever-increasing attention, as they are ideally suited for combinatorial synthesis (either on solid support or in solution) of libraries of products relevant to catalysis, such as agrochemicals or pharmaceuticals. Therefore, the study and implementation of MCRs possesses a wide range of appeal and applicability. A broad and expanding audience of scientists and students continues to apply the concepts of multi-component chemistry to an array of disciplines--this collection of research offers an angle for each and brings together the vast scope of possibilities within the greater community.